Asperger's and Girls: What Teachers Need to Know. Issue 2 (27th May 2015) - Jarman, Belinda; Rayner, Christopher
Abstract : Individuals with the pervasive developmental disorder Asperger's syndrome (AS) are generally of average or above average intelligence and attend mainstream schools. Despite their intelligence, some of the characteristics and challenges associated with AS can impact upon the quality of life they experience at school. Although both males and females are diagnosed with AS, females have been underrepresented and unrepresented in much of the AS research. Consequently, much of what is known about the school experiences of students with AS is based on studies consisting predominately of male perspectives. This article discusses what adult females with AS and parents of females with AS currently attending school wish teachers understood about AS in females. Many of the experiences described by participants indicate there is a lack of understanding about AS, both generally and specifically, in relation to females. Implications of these findings and recommendations for educators and schools are provided, and directions for future research are outlined.